The Influence of Foreign Insurance Affiliates, Market Share, Own Retention Ratio, Claims Ratio and Cost Ratio on the Performance of General Insurance Companies in Indonesia - Asep Iskandar; P. Basuki Hadiprajitno (Journal of Business, Social and Technology, 2023)
This study examines the effect of foreign insurance affiliation, market share, own retention ratio, claims ratio and expense ratio on the performance of general insurance companies in Indonesia. The performance of insurance companies in this study uses a measure of return on equity (ROE). The research population is all general insurance companies in Indonesia operating in 2018-2021. The research sample is 177 insurance companies in that period. Data collection uses financial reports submitted by insurance companies to the Financial Services Authority. Furthermore, to perform data analysis, multiple linear regression through the use of SPSS software as a tool is used in this study. The results show that foreign affiliation and own retention ratio have a positive impact on insurance company ROE. Meanwhile, market share, claims ratio, and expense ratio have a negative effect on ROE. Taken together, foreign affiliate, market share, own retention ratio, claims ratio and expense ratio affect ROE. The results of this study can provide an overview to regulators in regulating foreign ownership in the insurance industry in Indonesia as well as regulations regarding self-retention. For shareholders and management of insurance companies, this research can provide an overview of foreign cooperation policies and reinsurance policies associated with the risk profile of insurance business lines in Indonesia, fee policies, underwriting and claim handling.